SYMBOL OF WEALTHY IN THE GREAT GATSBY NOVEL - Lutfi Ahmad; Nadhira Azwa Irfani; Siti Alma; Vicko Destrada; Nurholis (Argopuro: Jurnal Multidisiplin Ilmu Bahasa, 2024)
The Great Gatsby is one of F. Scott Fitzgerald's most notable works, inspired by his personal experiences with wealth, love, and ambition, particularly reflecting his life on Long Island and his relationship with Zelda Sayre. The novel shows the Jazz Age, an era of extravagance in 1920s America, and analysed into the disillusionment of the American Dream, symbolized by Jay Gatsby’s story and journey. Gatsby's transformation from James Gatz and his lavish lifestyle are depicted as efforts to win Daisy Buchanan's love, but in the end reveal the emptiness of materialism. The novel also explores themes of identity, deception, and the moral decay of society, emphasizing the gap between old and new wealth. Symbolism plays a key role, with settings like East Egg and West Egg representing social class divisions, and Gatsby’s mansion symbolizing his hollow success. Through these symbols and themes, Fitzgerald critiques the pursuit of wealth as a path to happiness and illustrates the failure of the American Dream. Fitzgerald also uses colour symbols such as gold, silver, white, and yellow to show power and wealth in the novel.